Vasa previa: a case report - Mohapatra, Ipsita; Samantaray, Subha R.; Sindhuja, V. Naga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Vasa previa is defined as a condition where fetal vessels traverse the membranes in the lower segment below the presenting part unsupported by placental tissue or umbilical cord. Rupture of the membranes leads to fetal exsanguinations and even neonatal death. The etiology is uncertain, but risk factors include bilobed or succenturiate lobed placenta, velamentous insertion of cord, placenta previa, pregnancies resulting from In vitro fertilization (IVF) and multiple pregnancies. We report here a case of 24 year old woman, G3A2 at 34 weeks of gestation and history of 2 previous spontaneous abortions with vasa previa which was successfully managed. Prenatal sonographic diagnosis has the potential to improve or prevent the poor obstetric and neonatal outcome associated with it.